A Fractional Order Controller for Delay Dominant Systems. Application to a Continuous Casting Line - Copot, Dana; Ionescu, Clara (Journal of Applied Nonlinear Dynamics, 2026)
Continuous casting technology implies an exotherm process from liquid steel to solid slab. During this process, the temperature at the surface of the slab is one of the most important parameters for evaluating the cooling process and inherent material properties. To ensure a specific temperature gradient, several control elements need to be evaluated; e.g. to optimize casting speed, to determine intensity of the second cold and determine liquid depth. In this paper a fractional order control strategy is proposed to control the steel slab temperature, governed by delay dominant dynamics. The reference tracking for deisred temperature at end of casting line is evaluated by means of performance metrics. The results obtained indicate that the proposed methodology outperforms other strategies used for comparison.